2017
DOI: 10.1186/s12939-017-0592-0
|View full text |Cite
|
Sign up to set email alerts
|

Exploring breast cancer preventive lifestyle and social support of Iranian women: a study protocol for a mixed-methods approach

Abstract: BackgroundIt is widely accepted that a healthy lifestyle may decrease the probability of developing cancer. This study aimed to describe a study protocol that makes it possible to explore preventive health lifestyles of Iranian women and their received social support for the purpose of developing cultural strategies to increase breast cancer prevention.MethodsA mixed-methods study will be accomplished in two sequential parts. First, a cross-sectional study will be conducted in which 2,250 Iranian women are rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…There was also little report of childhood recreational PA, although a few women reported that they had engaged in recreational activities like swimming and cycling. This finding was consistence to previous studies in Iran that noted Iranian women have little discretionary personal time to engage recreational activities, and usually prefer sedentary leisure time activities as a form of entertainment such as watching television novellas [ 1 , 5 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…There was also little report of childhood recreational PA, although a few women reported that they had engaged in recreational activities like swimming and cycling. This finding was consistence to previous studies in Iran that noted Iranian women have little discretionary personal time to engage recreational activities, and usually prefer sedentary leisure time activities as a form of entertainment such as watching television novellas [ 1 , 5 ].…”
Section: Discussionsupporting
confidence: 88%
“…Further, most Iranian family members and friends holding jobs outside the home and have less time to be active with participants in regular PA or encourage them to use healthy diet. Several studies have reported that people are more likely to perform healthy behaviors when they feel their relatives and friends encourage them frequently to perform those behaviors [ 1 , 5 , 23 ]. Third potential explanation for significant negative effects of interpersonal influences on participation in healthy behaviors is probably due to high women responsibility for taking care of their children, therefore, these women lack of adequate time to involve in scheduled programs.…”
Section: Discussionmentioning
confidence: 99%
“…Prior-related behaviour is the main construct of the HPM model that influences individuals' characteristics and experiences (15,31) . In the first session of intervention, the participants with low education (under diploma level) lack appropriate experience in health-promoting behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most important factors that impacts on improving the quality of life of these patients is social support (7). Social support has a vital role in the quality of life and other outcomes after diagnosis and treatment of breast cancer (8,9). Social support exists in the form of both physical and psychological assistance from family, friends and others during di cult times (10).…”
Section: Introductionmentioning
confidence: 99%